ACADEMIC WRITING STRATEGIES: INTEGRATING LOGIC, CREATIVITY, AND COHESION IN SCHOLARLY ARTICLES - Musyafa, Wildayah; Sidiq, Muhammad Abdullah; Sunariyah, Sunariyah; Yuberti, Yuberti; Hamid, Abd. Rahman; Baharudin, Baharudin (Universitas Tanjungpura, 2026)
Academic writing is an essential skill for students, researchers, and professionals who aim to convey ideas, concepts, and findings systematically and logically. This article discusses the art of structuring ideas in scholarly writing by integrating formality, logic, and creativity to ensure the text remains both communicative and engaging. This study employs a literature review approach to analyze academic writing literature from various books, journals, and scholarly articles. The findings indicate that an effective academic style emphasizes clear formal language, valid references, and objectivity. Presenting arguments from general to specific, using examples and illustrations, creating an outline, developing paragraphs around a single main idea, and employing transitions between paragraphs are all strategies for effectively packaging ideas. The processes of revision, cohesion, coherence, and terminological consistency are also critical components in enhancing the quality of writing. This article concludes that writing in an academic style is a combination of the art of idea presentation and logical thought structure, resulting in scholarly work that is high-quality, easily understood, and engaging for readers.